Employee Performance on Public Services in Tana Toro Village, Pitu Riase District, Sidenreng Rappang Regency - Hasni. H; Andi uceng; Muhammad Arisal Asad (International Journal of Sustainable Applied Sciences, 2024)
At the Tana Toro Village Office, Pitu Riase District, Sidenreng Rappang Regency, this research aims to determine the effectiveness of employees in providing public services as well as the variables that influence the elements mentioned above. Rape. Quantitative descriptive techniques are used in this research methodology. The group studied consisted of 73 people who were provided services. Sampling of saturated samples (census) is the method used. Questionnaires, interviews, literature studies, and observations were used to collect data in this research. By using descriptive statistics using SPSS and percentages, the data is then processed and examined using a quantitative descriptive analytical approach. Research findings show that in Tana Toro Village, Pitu Riase District, Sidenreng Rappang Regency, employee performance was recapitulated with a percentage of 68%, while public services were recapitulated with a percentage of 66% in the same location. as well as variables that influence employee performance in public services in Tana Toro Village, Pitu Riase District, Sidenreng Rappang Regency, where 70% of the data was recapitulated.